Length-weight relationship and morphometric characteristics of Schizothorax spp. in the River Lidder of Kashmir - Bhat, F A; Yousuf, A R; Bhalki, M H; Mahdi, M D; Shah, F A (Indian Journal of Fisheries, 2016)
A study on the biology of fishes of River Lidder was carried out during 2003 – 2005. Seven species of fishes were collectedfrom the river, out of which, three commercially important species of Schizothorax viz., S. plagiostomus,S. esocinus and S. labiatus, dominated the catch both by number and weight. One hundred and thirty three specimens ofS. plagiostomus ranging in total length from 96 mm to 520 mm and in weight from 7 g to 948 g, 70 specimens of S. esocinusranging in total length from 57 mm to 420 mm and in total weight from 1g to 644 g and 40 specimens of S. labiatus rangingin length from 92 mm to 255 mm and in total weight from 7 to 179 g were taken for the study. The value of “n’ fluctuatedbetween 2.9467 to 3.0997. Length–weight relationship in S. plagiostomus was Log W = -4.9653 + 2.9467 Log L, forS. esocinus, Log W = -5.1635 + 3.0034 Log L and for S. labiatus, Log W = -5.2500 + 3.0997 Log L. S. esocinus showedmaximum growth in head length, pre-dorsal length, pre-pectoral length and eye diameter, while S. plagiostomus rankedsecond in pre-dorsal length. The maximum caudal fin length and pre-anal length was observed in S. plagiostomus. Themaximum body and peduncle depth was observed in S. labiatus. Due to low pollution load in the River Lidder, the environmentalstress on these species seems to be very low order and this has probably led to the almost ideal growth pattern of the three species.